Wigner function for Klein-Gordon oscillator in commutative and noncommutative spaces - Hassanabadi, S.; Ghominejad, M. (European physical journal plus, 2016)
. As a quasi-probability distribution function in phase-space and a special representation of the density matrix, the Wigner function is of great significance in physics. In this work, the Wigner function for the Klein-Gordon oscillator is studied in commutative and noncommutative spaces. We first study the Wigner function for Klein-Gordon oscillator in commutative space then, by using a generalized Bopp's shift method, we obtain the corresponding Wigner function in noncommutative space. The additional terms in Wigner function on a NC space is related to the noncommutativity of space.